Help wanted: Health care workers and mental health services. An analysis of six years of community concerns from North Dakota's oil boom residents. (October 2018) - Becker, Karin L.
Abstract: The research exploring the social impacts stemming from rapid growth in oil extraction communities has yielded two viewpoints: one that suggests increased economic development and opportunities and one that indicates social disruption and challenges. It has yet to be determined which hypothesis will be supported by the boomtown residents of western North Dakota. To better understand the extent of change communities in North Dakota have experienced, this article examines concerns derived from community health needs assessment data compiled over a span of six years. Seven community assessment reports are analyzed and aggregated to determine the overall prioritized community needs in the Bakken Formation of western North Dakota. Then, the community member feedback is analyzed using a grounded theory approach to better understand the prioritized needs. The community concerns are one way to understand the impacts of rapid growth and provide a snapshot of the extent of change residents have experienced due to an increase in population, wealth, and development. The community member feedback is used as a starting point to enter the corpus of boomtown literature and adds to our understanding of the social disruption theory. As the priority of concerns fluctuate over the years, the common thread of health care workforce shortage and mental health services remain prominent in rural North Dakota as well as energy extraction communities in America. Highlights: Applies social disruption theory to North Dakota's oil boom. Examines social impact of oil boom on community health services. Analyzes rural community impacts affected by extraction activities and management of critical resources. Emphasizes the role of community perceptions in health promotion strategies. Advocates for community-informed data to structure health policy planning.